1993
DOI: 10.1038/365764a0
|View full text |Cite
|
Sign up to set email alerts
|

Tumour-suppressor activity of H19 RNA

Abstract: Loss of heterozygosity in certain human embryonal tumours implicates a tumour-suppressor gene at chromosome 11p15.5 and selective loss of maternal alleles suggests that this gene is paternally imprinted. The human H19 gene maps to 11p15.5, is expressed in differentiating fetal cells and is paternally imprinted. We report here that two embryonal tumour cell lines, RD and G401, showed growth retardation and morphological changes when transfected with an H19 expression construct. More importantly, clonogenicity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
353
1
4

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 592 publications
(369 citation statements)
references
References 19 publications
11
353
1
4
Order By: Relevance
“…Plasmids pMEP-4H19B which contains the H19 cDNA under the control of the metallothionein promoter was a kind gift from Prof. Benjamin Tycko, Columbia University, New York and described in Hao et al (1993).…”
Section: Northern Blottingmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasmids pMEP-4H19B which contains the H19 cDNA under the control of the metallothionein promoter was a kind gift from Prof. Benjamin Tycko, Columbia University, New York and described in Hao et al (1993).…”
Section: Northern Blottingmentioning
confidence: 99%
“…These correlations and other experimental ®ndings can be explained by assuming the existence of a paternally imprinted (maternally expressed) tumor suppressor gene in this chromosomal area. In order to provide evidence for the proposal that H19 functions as a tumor suppressor gene, Hao et al (1993) introduced a construct expressing the H19 gene under the control of the metallothionein promoter into cells derived from a kidney tumor. Under conditions of high H19 expression, the cells, which showed prominent morphological changes, grew at a slower rate, had a much lower anchorage independent growth rate in soft agar, and did not develop tumors when injected into nude mice as did cells prior to their transfection with the H19 expression construct.…”
Section: Introductionmentioning
confidence: 99%
“…A tumor suppressor role was proposed by Hao et al (1993) who observed a decrease of tumorigenicity of a cancerous cell line (G401) in which an ectopic H19 gene was overexpressed. Rather indirect results obtained by several groups are in agreement with this tumor suppressor property of H19 (Moulton et al, 1994;Taniguchi et al, 1995;Cui et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…This pattern of expression suggests an involvement of H19 in fetal development. Although accumulating evidences suggest that H19 gene may play a role in oncogenesis (Lottin et al, 2002a), results from other studies suggest that it possesses a tumor-suppressor activity (Hao et al, 1993).…”
mentioning
confidence: 98%